Browsers, grazers or mix-feeders? Study of the diet of extinct Pleistocene Eurasian forest rhinoceros Stephanorhinus kirchbergensis (Jäger, 1839) and woolly rhinoceros Coelodonta antiquitatis (Blumenbach, 1799). (20th December 2021) - Stefaniak, Krzysztof; Stachowicz-Rybka, Renata; Borówka, Ryszard K.; Hrynowiecka, Anna; Sobczyk, Artur; Moskal-del Hoyo, Magdalena; Kotowski, Adam; Nowakowski, Dariusz; Krajcarz, Maciej T.; Billia, Emmanuel M.E.; Persico, Davide; Burkanova, Elena M.; et al.
Abstract: The wooly rhinoceros ( Coelodonta antiquitatis ) and forest rhinoceros ( Stephanorhinus kirchbergensis ) were prominent representatives of the Middle and Late Pleistocene glacial and interglacial faunas of Eurasia. Their diet has traditionally been inferred on functional morphology of the dentition and skull. In rare cases, food remains are preserved in the fossas of the teeth or as gut content. New approaches to infer diet include the study of isotopes and mesowear. Here we apply all four methods to infer the diet of these emblematic rhinoceros' species and compare the food actually taken with the food available, as indicated by independent botanical data from the localities where the rhinoceros' fossils were found: Gorzów Wielkopolski (Eemian) and Starunia (Middle Vistulian) as well as analysis of literature data. We also made inferences on the season of death of these individuals. Our results indicate that the woolly rhino in both Europe and Asia (Siberia) was mainly a grazer, although at different times of the year and depending on the region its diet was also supplemented by leaves of shrubs and trees. According to the results of isotope studies, there were important individual variations. The data show a clear seasonal variation in the isotope composition of this rhino's diet. In contrast, Stephanorhinus kirchbergensis was a browser, though its diet included low-growing vegetation. Its habitat consisted of various types of forests, from riparian to deciduous and mixed forests, and open areas. The diet of this species consisted of selected items of vegetation, also including plants growing near both flowing and standing waters. The food remains from the fossae of the teeth indicated flexible browsing, confirming the previous interpretations based on functional morphology and stable isotopes. Long-term data from mesowear and microwear across a wider range of S. kirchbergensis fossils indicate a more mixed diet with a browsing component. The different diets of both of rhinoceros reflect not only the different habitats, but also climate changes that occurred during the Late Pleistocene.